PTH-105 hospital admission in patients with advanced chronic liver disease due to non-alcoholic fatty liver disease. (8th June 2018) - Shearer, Jessica; Driver, Robert; Taylor, Eleanor; Chizhande, David; Jones, Rebecca; Rowe, Ian
Abstract : Introduction: Individuals with non-alcoholic fatty liver disease (NAFLD) often have multiple medical comorbidities. The development of advanced chronic liver disease is considered a defining point in the natural history of NAFLD. The aims of this study were to pilot the use of electronic health record (EHR) follow-up of patients with NAFLD and to assess the frequency of clinical events due to both complications of liver disease and also non-liver related causes. Methods: Transient elastography data was collected from St James's University Hospital in Leeds between 2012–2017 Patients were defined as having advanced chronic liver disease based on liver stiffness measurement (LSM) >10 kPa and were analysed in two strata:≥10–15 kPa, and >15 kPa. Hospital admissions and mortality were recorded from data submitted to NHSDigital, and sub-divided into liver-related and non-liver related causes. Results: The study included 486 patients: 303 (62%) male, mean age 56 years. Median follow-up interval was 24 months. Data regarding admissions is summarised in table 1. Four patients (all with LSM >20 kPa) were admitted on eight occasions with decompensation as a primary diagnosis code (5 admissions with hepatic encephalopathy, 2 variceal bleeding and 1 ascites). Four patients had primary diagnosis codes for hepatocellular carcinoma. Overall, liver-related events accounted for a minority of admissions. Considering inpatient admissions, only 1 in 5 admissions were for complications of liver disease, even amongst those individuals with LSM >15 kPa (table 1). The most common causes of non-liver related admission according to ICD-10 code were gastrointestinal (14%), cardiovascular (11%), musculoskeletal (10%) and respiratory (9%). Overall 17/486 individuals (3.5%) had died (5 patients≥10–15 kPa; 12 patients>15 kPa). Liver disease was listed as a contributing factor in a minority of cases (5/17, 29%). Conclusions: EHR can be used to accurately define outcomes in patients with advanced chronic liver disease due to NAFLD. The finding that liver related morbidity and mortality accounts for only 1 in 5 clinical events for patients with NAFLD and advanced chronic liver disease will significantly reduce the effectiveness of novel therapeutics in development for this patient group.